School Based Mental Health Promotion and Literacy: A Thematic Review of Programs, Frameworks, and Implementation Challenges - Popy Mayasari Afendy; Eka Sakti Yudha; Syamsu Yusuf; Ipah Saripah (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
Adolescent mental health has become an increasingly urgent global concern, with schools recognised as strategic settings for mental health promotion, prevention, and early intervention. Over the past two decades, a wide range of school-based mental health initiatives have been developed, including mental health literacy programs, universal preventive interventions, teacher capacity-building, and whole-school approaches. However, existing evidence suggests that many initiatives remain fragmented and primarily focused on short-term outcomes. This article aims to synthesise international literature on school-based mental health initiatives in order to identify dominant trends, methodological limitations, and directions for sustainable development. A narrative thematic literature review was conducted using peer-reviewed studies published between 2004 and 2025 that examined mental health programs, frameworks, and assessment practices within school settings. The findings indicate that mental health literacy and universal preventive programs consistently improve students’ knowledge, attitudes, coping skills, and perceived readiness to seek help, while teacher-focused training enhances educators’ confidence and preparedness to support student mental health. Nevertheless, evidence of sustained behavioural change, system-level integration, and long-term effectiveness remains limited. In addition, considerable heterogeneity in assessment tools constrains comparability across studies and weakens cumulative evidence building. This review concludes that advancing sustainable school mental health systems requires integrated whole-school and multi-tiered approaches, strengthened teacher capacity embedded within supportive school structures, and the use of standardised, culturally adaptable assessment strategies.